BIOMARKER DISCOVERIES AND POTENTIAL BIOMARKERS IN LUNG CANCER : A NARRATIVE REVIEW - Andika Dwi Mahendra; Muhammad Hatta Prabowo; Aisyah Fitriannisa Prawiningrum (Universitas Muhammadiyah Surakarta, 2023)
Lung cancer is the second most common cause of death worldwide after breast cancer. This is associated with late diagnosis, which reduces the survival rate. Early diagnosis is one approach that may be employed to improve outcome for the patient with lung cancer. When a small level of cancer is present in the body, a biomarker can be utilized as a diagnostic marker. Liquid biopsy is minimal invasive which can be done to obtain multi-biomarkers in lung cancer. In this article, we will discuss and explore about potential biomarkers for lung cancer early diagnosis.